Existence of monotone equilibria in first-price auctions with resale - Charles Z. Zheng (The University of Western Ontario, Economic Policy Research Institute (EPRI), 2014)
Existence of a monotone pure-strategy perfect Bayesian equilibrium is proved for a multistage game of first-price auctions with interbidder resale, with any finite number of ex ante different bidders. Endogenous gains at resale complicate the winner's curse and upset previous fixed-point methods to prove existence of monotone equilibria. This paper restructures the fixed-point approach with respect to comparative statics of the resale mechanisms strategically chosen after the auction. Despite speculation possibilities and the discontinuity-inducing uniform tie-breaking rule, at our equilibrium any bid that stands a chance to win is strictly increasing in the bidder's use value.
Keywords: 330